DEVELOPMENT OF ORGANIZATIONAL MANAGEMENT IN IMPROVING BUSINESS SUSTAINABILITY IN STRUCTURAL KEBANAN (WINNER OF THE STUDENT DIGITAL ENTREPRENEURSHIP INNOVATION CHAMPIONSHIP) - Hadi, Syamsul; Kirana, Kusuma Candra; Cahyaning, Enggar Kartika; Grace, Flora; Rokhman, Nur; Wildan, Muh Khaerul; Salma, Syarifah; Choirunnisa, Ayu Rizka; Iswantoro, Ibnu Yanuar; Andleeb, Naima (SMARTINDO, 2023)
Background- KEBANAN is one of the on demand service platforms created by students at Bachelorwiyata Tamansiswa University as a result of the Student Digital Entrepreneurship Innovation Program championship of the Indonesian Ministry of Education and Culture. KEBANAN is based on a mobile application that can provide a solution to banan when experiencing problems on the road with the tagline